Is Electronic Health Literacy Associated with Learning Outcomes among Medical Students in the First Clinical Year?: A Cross-Sectional Study - Krittai Tanasombatkul; Kanokporn Pinyopornpanish; Chaisiri Angkurawaranon; Nida Buawangpong; Auswin Rojanasumapong; Wichuda Jiraporncharoen (MDPI AG, 2021)
Medical students tend to use the internet as a primary resource when seeking health information. This study aims to assess the patterns of internet use, eHL level, and learning outcomes with eHL among medical students at Chiang Mai University. A cross-sectional study was conducted among 88 medical students in the first clinical year. The eHL level was determined using the Thai version of the electronic Health Literacy Scale or eHEALS. The patient case report scores were obtained representing the learning outcome. Linear regression was used to identify factors influencing their eHL level and case report scores. Students recognized the importance and usefulness of the internet. The mean eHEALS score was 33.45. There was a lower degree of agreement on questions regarding internet usage, having skills to evaluate the resources, and confidence in using health information to make health decisions. The eHEALS score had no statistically significant association with most variables and case report scores, but with the longer time of internet use (p-value = 0.014). Although medical students perceived that they have high eHL levels, they report lower confidence in using the information. Including critical thinking skills for electronic health information in the medical curriculum could be useful.